الإستحسان بالعرف و مقاصده عند الإمام ابن العربي - *فاطنة بثينة عمري; *ميرة سليماني; د/محمد عيشوبة (جامعة عمار ثليجي الاغواط, 2023)
اندندب ال دادد مدل الأ يدداأ الشرعيدة علد الأعد ا ر ع ال دا ا ع ع دنا ممدا اددل لندا ميبهداع ع مد اعببا الشا د الحييدم لهاع ع مد مشرععيبهداع ف دد اعبند ا مداأ ابدل ال ربي في مبانك ياأ ال رآذ عل ت يد الدن الشدرعيع ع بندا ال دادد مدل الأ يداأع ع ا ل ال در ع ع دنا لم ا رعدا الم ا دد الشدرعية للميلددع ع مدل بديل دم مدا تدمَّ اببنا عل الأع ا ر ع ال ا ا . ع د تو لب ا سبندا ن ل بياذ الأ ياأ البي اسبحسدنها ا مداأ ابدل ال ربدي مدل اا مبانك ياأ ال رآذع ع بياذ م د مل تل الأ ياأع فل ع ا ر تدتثير عاسد علد يدداأ الميلدددع ع دنا لم ا رعاتهدا م ددد البيسديرع ع فد الحدر ع ع البسدهي علد الميلددد. الهلمات المعتاحية: ا ماأ ابل ال ربيع الاسبحسداذع ال در ع الم ا ددد. Abstract: Many of the legitimate provisions have been based on habits, and this is what is so important to us. How wise the street is, and how legitimate it is, Imam Ibn al-Arabi in his book The provisions of the Koran took care of the capture of the legal text and the construction of many provisions, their response to custom, and this is to accommodate the legitimate purposes of the cost, One of the most important things that has been built on customs and customs. This study has shown the provisions that Imam Ibn al-Arabi desired through his book The Provisions of the Qur 'an, and the purpose of those provisions. The customs have a wide impact on the provisions of the cost, taking into account the purpose of facilitating, raising the embarrassment, and facilitating the cost. Keywords: Imam Ibn al-Arabi, Al-Tahassan, custom, Al-Maqdad